Antibacterial Activity of Cinnamaldehyde and Carvacrol against Foodborne Pathogens and Spoilage Bacteria - Saha, Shikha Rani; Bari, ML; Inatsu, Y; Kawampto, S; Hoque, Md Mahfuzul (Bangladesh Journal of Microbiology, 2019)
The excessive use of chemical preservatives is a serious problem worldwide, which necessitates the discovery of new classes of antimicrobials from other sources like herbs and spices for preservation of food and/or food products. In this study, antibacterial activity of essential oils (EOs) such as cinnamaldehyde and carvacrol were tested against four foodborne pathogens viz Staphylococcus aureus ATCC 25923, Shigella dysenteriae-I MJ-84, Escherichia soli ATCC 25922, Vibrio cholerae ATCC 6395 and two food spoilage bacteria viz Pseudomonas aeruginosa ATCC 27853 and Klebsiella rhizophila ATCC 13882, respectively, using disc diffusion method. These EOs were found to inhibit both categories of bacteria. Cinnamaldehyde and carvacrol showed maximum 30.0 ± 0.2 and 27.5 ± 0.5 zones of inhibition, respectively against S. aureus. Pseudomonas aeruginosa was found resistant against carvacrol. Cinnamaldehyde and carvacrol was determined. Both showed antibacterial activity after treatment at 100°C for 30 min suggesting that high temperature does not affect the activity. Both the EOs have a broad pH range and exhibited highest activity at pH 7.0, suggesting that they remain un-dissociated at pH change. The MIC and MBC values of cinnamaldehyde ranged between 0.125 and .0 %, and 0.25 and 2.0 %, respectively and MIC and MBC values of carvacrol ranged between 0.125 and 0.5%, and 0.25 and 1.0 %, respectively. The results of this study confirmed the possibility of using cinnamaldehyde and carvacrol in preventing the growth of foodborne pathogens and spoilage bacteria and extend the shelf life of foods. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 91-96